KDM3A and KDM3B regulate alternative splicing in mouse pluripotent stem cells - Caleb M. Dillingham; Harshini Cormaty; Ellen C. Morgan; Andrew I. Tak; Dakarai E. Esgdaille; Paul L. Boutz; Rupa Sridharan (iScience)
Summary: Histone modifying enzymes are crucial in preserving cell identity by establishing a conducive chromatin environment for lineage specific transcription factor activity. Mouse pluripotent embryonic stem cells (mESCs) show lower levels of gene repression associated with histone modifications, facilitating rapid response to differentiation cues. The KDM3 family of histone demethylases removes repressive histone H3 lysine 9 dimethylation (H3K9me2). We uncover a surprising role for the KDM3 proteins in the post-transcriptional regulation of mESCs. Proteomic analysis shows KDM3A and KDM3B interacting with RNA processing factors such as EFTUD2 and PRMT5. Acute degradation of the endogenous KDM3A and KDM3B proteins resulted in altered splicing independent of H3K9me2 status or catalytic activity. These splicing changes partially resemble the splicing pattern of the more blastocyst-like ground state of pluripotency and occur in important chromatin and transcription factors such as Dnmt3b and Tcf12. Our findings reveal non-canonical roles of histone demethylating enzymes in splicing to regulate cell identity.